Analysis of the release pattern of floral aroma components of Rhus chinensis based on HS-SPME-GC-MS technique - Ju Gu; Yun Niu; Yiting Tang; Ping Liu; Yandi Wu; Zixiang Yang; Chao Wang (PLoS ONE, 2025)
Rhus chinensis, a native plant species of China, possesses significant economic value in the ornamental sector. This study investigates the floral fragrance components and release patterns of R. chinensis, thus providing a theoretical foundation for the utilization of its floral fragrance. Headspace-solid phase microextraction (HS-SPME), gas chromatography-mass spectrometry (GC-MS), and chemometrics were used in conjunction with principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA) to identify the essential components of the floral aroma during the budding, blooming, and withering stages of R. chinensis. The important components of the aroma were also indicated by using the Variable Importance Projections (VIP) and Kruskal-Wallis nonparameters (P). The floral scent components of R. chinensis were abundant; 91 and 84 types of floral compounds were found throughout varying flowering seasons and daily patterns, respectively. The primary compounds responsible for flower odors were terpenes, representing over 70% of the floral aroma. Significant fluctuations were observed in the composition of 18 essential scent components and 21 chemicals, with daily variations observed in various flowering stages. The types of floral scent substances continued to rise during the flowering process; however, the relative concentrations of the floral aroma components of R. chinensis initially climbed and then fell, reaching 3.60μg/g at the full flowering stage and only 2.40μg/g after the withering stage. In the course of the daily shift, the release amount increased during the day compared to the night, peaking at 4.80μg/g. The substance type reached its greatest point at 12:00, making the circadian rhythm change rule evident. This study provides a reference for the further development and utilization of the flower fragrance of R. chinensis.